Gender research on the physician-patient relationship - Palomar Mingote, Paula (Filanderas, 2020)
This paper presents part of the results of an international systematic literature review that analyzes 42 studies selected by pre-established criteria out of the 238 found in Medline/Pubmed between 1966 and 2020. First, we show the scientific conceptual framework and professional values in which a patient-centered medical practice can be developed, investigating the patriarchal tradition that guides and bases the current physician-patient relationship and defining the problems that have emerged from a feminist view: differential morbidity, gender bias, androcentrism, and professional disparity. Having indicated the methodology of the study and the main bibliometric results, in the second part the contributions of narrative studies found in the review are examined in detail, as well as the most prevalent problems identified among the observational and meta-analytical studies. We conclude by making ours the maxim that emerges from this study: it is essential to know and be aware of the effect of gender differences in the physician-patient relationship given the evidence that continuous education of professionals in clinical interpersonal communication is an effective tool to control and avoid sexist attitudes and androcentric bias in the regular clinical practice.
Keywords: Physician-Patient Relations; Clinical Interview; Bibliometrics; Gender Bias; Feminism